Kontribusi Pondok Pesantren Darul Mukhlisin dalam Peningkatan Pendidikan Agama Islam Di Desa Sumber Kejayan, Kecamatan Mayang, Kab. Jember - Sofiatus Sobriyah (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2021)
Society will always be faced with a civilization that always develops from time to time. These developments have resulted in a shift, namely a shift from the agrarian period to industry and the rolling of the information age and globalization. The occurrence of very rapid development is caused by human resources whose quality of education can be reliable. The problem of education for developing countries such as Indonesia is very important for the continuity of the life of the nation and the country itself. The existence of education will ensure the continuity of development that is being promoted by the government. The success of development depends a lot on education, in other words, without education, development will be neglected. The emergence of preparation efforts which are generally based on the needs of the nation who want the nation's next generation to be better than now. Because thus the younger generation can grow and develop both physically and spiritually in line with the educational process experienced. Islamic boarding schools as one of the educational institutions in Indonesia make a very large contribution to the world of education. The general purpose of Islamic boarding schools can support the achievement of the goals of national education, namely realizing people who believe and have piety as well as humans who are useful for the nation. So the focus of that goal is the balance of life on earth and the hereafter. As for the method that we will use, the first is by taking a research approach, in this study qualitative research is used. Second, Determination of Population and Sample. Third, Data Collection Methods (Observation Methods, Interview Methods, Documentation Methods, Data Analysis Methods) From the results of the study stated that the Darul Mukhlisin Islamic Boarding School in its development has undergone many changes, including the education system both in teaching methods and institutionally, including the expansion of educational institutions including Islamic Elementary School, Tsanawiyah Madrasah, Agrotechnology Vocational School and Diniyah madrasah for early childhood and for cottage children itself. Social Community, Physical Condition of Darul Mukhlisis Islamic Boarding School, Daily Activities at Darul Mukhlisin Islamic Boarding School.